ETIKA SOPAN SANTUN SISWA KELAS V DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR NEGERI 106211 KAMPUNG PADANG - Dewi Nurhasanah Nasution (LP3M KH Yazid Karimullah Institute, 2022)
It is very important to apply students' courtesy ethics in learning in elementary schools, such as students' polite ethics when communicating with teachers and fellow classmates. This study intends to observe and explain students' etiquette to friends and teachers during learning activities in elementary schools. The object of study is the learning activity in the fifth grade of the State Elementary School 106211 Kampung Padang. The study subjects were fifth grade students. The data collection technique in this study used observation and interview techniques. In harmony with the data that has been obtained by the researcher, the results of the study explain that there are still students who have good manners with their teachers and fellow friends who are not good. Based on interviews, the teacher has often taught good etiquette such as ethics in communication and behavior when dealing with teachers and fellow friends, but because of the background and environmental factors of students who are not good, not all fifth grade students at State Elementary School 106211 Kampung Padang have ethics. poor manners when the learning process is in progress.